The relationship between perceived teacher support and student engagement among higher vocational students: A moderated mediation model - Xu, Xiuni; Wu, Zhen; Wei, Dongpo (Frontiers in Psychology, 2023)
Introduction Student engagement is a best predictor variable of student’ development and success. It can be highly influenced by internal and external environmental factors, such as perceived teacher support. Methods In order to explore the influence of perceived teacher support on student engagement among higher vocational students, this study conducted a questionnaire on 1,136 Chinese higher vocational students using perceived teacher support, basic psychological needs satisfaction, learning drive, student engagement and Optimistic attributional styles for explaining positive events (OAS_P) five scales. Results The results show that: (1) Perceived teacher support can’t indirectly predict the student engagement among higher vocational students through basic psychological needs satisfaction; (2) Perceived teacher support can indirectly predict student engagement through learning drive; (3) Perceived teacher support can indirectly predict student engagement through basic psychological needs satisfaction and learning drive; (4) OAS_P has a significant moderation effect on both learning drive and student engagement. Discussion The finding of this study stated that perceived teacher support has a significant influence on student engagement. So in the teaching process, teachers should pay attention to their learning psychology, provide them with various support and encouragement and beneficial guidance, stimulate their learning drive, help them form a positive and optimistic attribution style, and make them actively participate in learning and school life.